DESCRIPTIVE ANALYSIS: THE IMPACT OF TECHNOLOGICAL PROGRESS ON TRADISIONAL COMMUNITIES AND MODERN SOCIETY - Hanifah Pratiwi; Firman Firman; Riska Ahmad (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Technological advances affect changes in society, both in traditional societies and modern societies. The aim of this research is to see the effect of technological advances on traditional and modern societies. This study uses a literature review. The author uses data collection techniques by collecting and analyzing information from sources that are relevant to the discussion. The findings of this study are that there are differences in mindset, culture, beliefs, place of residence, tools used, clothes used, language used, and social life, the medium and transformation between traditional society and modern society as a result of technological advances. The impact of technological advances and modernization can also have negative impacts such as the fading or withering away of norms or values ??in certain societies, causing modern humans to place more importance on their personal lives without regard for the wider community. Therefore it can be concluded that there is a change in traditional society and modern society which is the impact of technological advances that are currently developing